Current treatment for male infertility: an umbrella review of systematic reviews and meta-analyses - Jian-Jun Ye; Ze-Yu Chen; Qi-Hao Wang; Xin-Yang Liao; Xing-Yuan Wang; Chi-Chen Zhang; Liang-Ren Liu; Qiang Wei; Yi-Ge Bao (Asian Journal of Andrology)
This umbrella review aimed to summarize and provide a general evaluation of the effectiveness of current treatments for male infertility and assess the quality of evidence and possible biases. An umbrella review of systematic reviews and meta-analyses available in PubMed, Web of Science, and Scopus, covering studies published up to October 2023, was conducted. Sperm concentration, morphology, and motility were used as endpoints to evaluate the effectiveness of the treatments. Of 2998 studies, 18 published meta-analyses were extracted, yielding 90 summary effects on sperm concentration (n = 36), sperm morphology (n = 26), and sperm motility (n = 28) on 28 interventions. None of the meta-analyses were classified as having low methodological quality, whereas 12 (66.7%) and 6 (33.3%) had high and moderate quality, respectively. Of the 90 summary effects, none were rated high-evidence quality, whereas 53.3% (n = 48), 25.6% (n = 23), and 21.1% (n = 19) were rated moderate, low, and very low, respectively. Significant improvements in sperm concentration, morphology, and motility were observed with pharmacological interventions (N-acetyl-cysteine, antioxidant therapy, aromatase inhibitors, selective estrogen receptor modulators, hormones, supplements, and alpha-lipoic acid) and nonpharmacological interventions (varicocele repair and redo varicocelectomy). In addition, vitamin supplementation had no significant positive effects on sperm concentration, motility, or morphology. Treatments for male infertility are increasingly diverse; however, the current evidence is poor because of the limited number of patients. Further well-designed studies on single treatment and high-quality meta-analysis of intertreatment comparisons are recommended.